A Study on the European Union's Secondary Use System of Health Data and Its Insights - Yao PAN (Yixue yu zhexue, 2025)
The effective utilization of health data not only contributes to improve the treatment quality for individual patients，but also promotes the efficient realization of public interests in areas such as healthcare governance, medical research, and public health management. The European Union has been exploring the establishment of a system for the secondary use of health data, to maximize the value of health data applications and alleviate concerns of data subjects about potential infringement of their rights. This paper provides a comprehensive analysis of this system, with a particular focus on purpose limitation, authorization mechanisms, and the right to object and its exceptions and limitations. Based on these observations, it is suggested that China could enhance the application of health data by defining permissible purposes for secondary use, improving independent and tiered authorization mechanisms, and establishing the right to object and its exceptions and limitations. These measures are intended to unlock the intrinsic value of health data and promote its efficient application.